Bone Metastasis From Gastric Adenocarcinoma—What Are the Risk Factors and Associated Survival? A Large Comprehensive Population-Based Cohort Study - Huang, Lei; Zhao, Yajie; Shi, Yan; Hu, Weiguo; Zhang, Jun (Frontiers in Oncology, 2022)
Background: While bone metastasis is not common in gastric adenocarcinoma (GaC), it can have important impacts on prognosis. This large cohort study aimed to explore factors associated with bone metastasis in GaC, and to investigate the time-dependent cumulative mortalities and prognostic factors in GaC patients with bone metastasis at the population level. Methods: Data on patients with GaC diagnosed in 2010-2016 were retrieved from a large population-based database. We explored factors associated with bone metastasis using the multivariable-adjusted logistic model. We then calculated the time-dependent cancer-specific mortalities in GaC patients with bone metastasis using the cumulative incidence function, and compared mortalities across subgroups using Gray’s test. We further assessed factors associated with mortality using the multivariable-adjusted Fine-Gray subdistribution hazard model. Results: Together 11,072 eligible patients with metastatic GaC were enrolled, who included 1511 (14%) people with bone metastasis and 9561 (86%) with other metastasis, encompassing 6999 person-years of follow-up. Bone metastasis was more frequently detected in 2014 or later, in younger patients, in patients with gastric cardia cancers, in people with signet-ring cell carcinoma, and in those with poorly-differentiated/undifferentiated cancers; it was less commonly observed in black patients. Bone metastasis was associated with more frequent brain and lung metastases. The median survival of patients with bone metastasis was 4 months; the 6-month and 3-year cancer-specific cumulative mortalities were 56% and 85%, respectively. In patients receiving chemotherapy, American Indians/Alaska Natives, patients with gastric antrum/pylorus cancers, and those with positive lymph nodes had higher mortality risks, while those undergoing resection had lower mortality hazards. Conclusion: In GaC patients bone metastasis was associated with various clinicopathologic factors including age, ethnicity, tumor location, histology, differentiation, and metastasis to other sites. Patients with bone metastasis had poor prognosis which was associated with ethnicity, tumor location, lymph node involvement, and treatment. Our findings provide important hints for tailed patient management and for further mechanistic investigations.